Upaya Peningkatan Hasil Belajar Kelompok Siswa Dengan Metode Ceramah melalui Strategi Pembelajaran Peningkatan Keterampilan Berpikir (SPPKB) pada Bidang Studi IPS Terpadu di SMPN 2 Jerowaru - Muhamad Zaril Gapari (PALAPA, 2021)
Education is one that everyone should follow. With adequate education someone will be able to answer the global challenges in life. With this education also the dignity of a person will be lifted, the lower the level of education of a person, the dignity of the environment is also low. The dignity of the Indonesian nation in the eyes of the world is also influenced by the education of its population. One indication of the achievement of the education process is the realization of satisfactory learning outcomes. Education can be said to be successful if good learning outcomes are achieved or students get grades above average. The purpose that has been determined in this study, namely to improve student group learning outcomes with the lecture method through learning strategies to increase thinking skills (SPPKB) in the integrated IPS subject for class VII at SMP N 2 Jerowaru. Therefore, to achieve this goal, the researchers tested 28 students as samples with 11 male and 17 female samples taken from the total population. This type of research is classroom action research (PTK) which consists of two cycles and each cycle consists of two meetings. The research instrument used to determine the level of understanding of students was a descriptive test (subjective) which was then analyzed by learning completeness criteria, while to determine the activities of students and teachers using observation sheets. Based on the results of the research, after analyzing the data, it was obtained data on students' understanding of cycle I in student discussion group activities of 74.4% with an average of 2.6 and 50% completeness of student learning with an average of 59.3. while in cycle II the percentage of student discussion group activities was 87.2% with an average of 3.1 and the percentage of student learning completeness as much as 89.1% with an average value of 72.1.